Medjunarodni promet meda – stanje i tendencije. Agroekonomika - Vlahović Branislav; Plavša Nada; Riste Elenov (Департман за економику пољопривреде и социологију села Пољопривредног факултета Универзитета у Новом Саду, 2020)
The paper analyzes the international trade in honey. The analysis determined the changes in the international trade, the largest exporters and importers as well as trade flows of honey. The data source was the statistical database of the International Trade Center (ITC) for the pe riod 2015-2019. The average world export of honey amounted to 660 thousand tons, with a trend of slight growth at a rate of 0.31% annually. The value of the world export of honey amounted to 2.2 billion US dollars. The world's largest exporter is China, which is also the world's largest producer with production of 129 thousand tons, accounting for 19.6% of the world export. The world's largest importer of honey is the United States with production of 186 thousand tons, accounting for 27.6% of the world import. The achieved turnover was influenced by relatively low consumption of honey in the world, which is at the level of 0.25 kilograms per capita annually.
INTERNATIONAL TRADE IN HONEY – CURRENT STATE AND TRENDS
Keywords: honey; international trade; export; import; price